Barrancabermeja y su gastronomía, un tesoro poco explorado - Cañas Carvajal, Paul David; Capacho Tirado, Diego Fernando; García Rodríguez, Hilda Lorena; Holguin Mariño, Margareth Julyana (La Tercera Orilla, 2019)
Experiencia del programa de Gastronomía y Alta cocina